POTENSI EKSTRAK DARI LIMBAH KULIT KAYU DAN BATANG MURBEI (Morus alba var. kanva) SEBAGAI ANTIBAKTERI Enterococcus faecalis ATCC 29212 - Chandra Dyah Alifia; Fathul Yusro; Yeni Mariani (Universitas Tanjungpura, 2019)
There are several species of mulberry that grow and cultivated in Indonesia, and Morus alba var. kanva is one of it. The leaves of mulberry are used as silkworm feeds, while the bark and stem as waste are not utilized. This study aims to analyze the potency of bark and stem of mulberry as an antibacterial Enterococcus faecalis (E. faecalis) which is a cause of the infection of teeth root canal. The bark and stem of mulberry were measured it water contents then macerated with ethanol and the percentage of yield extracts were determined. Furthermore, anti-bacterial activites were conducted with 5 level concentrations of bark and stem extract (25; 50; 75 and 100 mg / mL), ethanol and Tetracycline 250 mg as negative and positive control. The results showed that the bark had a moisture content of 10.7% with a yield value of 25.5%, while the stem had a moisture content of 9.4% and a yield value of 9.8%. the optimum concentration is at the level of 75 mg / mL because at this concentration it has been able to inhibit the inhibitory zone value which is no different from 100 mg / mL.